Fine Motor Skills in Attention Deficit Hyperactivity Disorder and Developmental Coordination Disorder - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2006)
The manual dexterity subtests of the Movement Assessment Battery for Children, and handwriting and computerized graphomotor tasks were used to investigate motor skills of a group of 12 children (11 males, 1 female; mean age 9 years 7 months) with attention deficit hyperactivity disorder (ADHD) and developmental coordination disorder (DCD) and 12 controls at University Medical Centre Groningen, the Netherlands.